Job demand and control among clinical nurses in a provincial hospital and related factors: Results from a cross-sectional study in 2020. - Tran Thi Thu, Thuy; Nguyen Thi, Huong; Nguyen Van, Bang; Le Thi Thanh, Xuan (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2021)
Objective: This study aimed to examine the psychological work environments and associated factors among clinical nurses in a provincial tertiary hospital in the North of Vietnam in 2020.Methods: A cross-sectional survey was conducted among all nurses of 22 clinical wards who directly provided care to patients. 261/318 eligible nurses returned the self-reported survey questionnaires that consisted of the Vietnamese version of the Job Content Questionnaire 22 items and originally developed questions on personal characteristics and work conditions. Descriptive analysis, t-test, ANOVA, and multivariate linear regressions were applied to describe the current job demand, job control, and related factors at the significant level p less than 0.05.Results: The response rate of the current study was 82.1%. Nurses reported moderate job demand (29.39±3.64) and job control (66.86±5.79). Increased job control was significantly associated with more frequency of receiving support from superiors (p
Keywords: Job demand; Job control; JCQ; clinical nurses; provincial hospital; Vietnam